2012
DOI: 10.2528/pierc11120610
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Bandpass Filters Using Parallel-Coupled Sirs With Wide Spurious Supprression

Abstract: Abstract-This paper proposes parallel-coupled stepped impedance resonators (SIRs) used for wideband bandpass filters with reduced size and improved spurious response suppression in out-of-band. The filter design concept is demonstrated by both two-and four-parallel coupled line resonator structures with the same fundamental frequency (f 0 ) of 6.5 GHz. The first bandpass filter has been designed using two resonators with λ/2 slot and embedded slot feeds for spurious response suppression at 2f 0 and 3f 0 , resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Wireless communication systems today make tremendous demands of compact high performance microwave bandpass filters (BPFs), ultra-wideband applications of information systems have promoted the development of wideband filter technology. Many different approaches have been developed for achieving wideband operation in wideband bandpass filters [1][2][3][4][5][6][7][8][9][10][11]. Stepped impedance resonators (SIRs) have been proved suitable for wideband applications due to their multimode characteristics [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Wireless communication systems today make tremendous demands of compact high performance microwave bandpass filters (BPFs), ultra-wideband applications of information systems have promoted the development of wideband filter technology. Many different approaches have been developed for achieving wideband operation in wideband bandpass filters [1][2][3][4][5][6][7][8][9][10][11]. Stepped impedance resonators (SIRs) have been proved suitable for wideband applications due to their multimode characteristics [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Some papers show that the filter's characteristics are a consequence of general network configurations, like [3] that demonstrated that the parallel connection of the two port networks has features that can be used for designing microwave BPFs, or [4] that shows that the using of a 0 • feed structure creates two extra transmission zeros at the frequencies close to and on the opposites of the passband. A conclusion that some distinctive characteristics of the filters, such as the number and positions of the transmission and reflection zeroes, are a consequence of their topology, can be reached based on the similar characteristics of BPFs described in [5][6][7][8][9][10][11][12][13][14], distinguished by the authors into different kinds and analyzed and designed by different methods. The correlation between the topology and the electrical characteristics is especially noticeable for BPFs with capacitive coupled resonators [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%